Penerapan Best Practices Pengelolaan Keuangan Negara Pada Sektor Pengadaan Barang Dan Jasa Pemerintah Sebgai Upaya Mewujudkan Good Governance - Hendrawan, Rikki (Widya Yuridika, 2025)
In practice, a lot of irregularities occur in the process of procuring goods and services both in the budget planning process, the procurement preparation process, the process of implementing the procurement of goods and services, handing over payments and in the process of monitoring and accountability. The procurement of government goods and services is indeed a wetland for a number of individuals to commit corruption. The purpose of the research is to provide a new perspective in solving the complexity of problems in the procurement of government goods and services and analyse existing problems in order to reduce legal problems in the procurement of goods / services, especially related to the formulation of problems in this study, namely How is the mechanism of procurement of goods and services in the frame of current concepts and realities and secondly, How is the best practice of financial management in the procurement of government goods and services. This research is a normative research that uses literature study. The data collection method is carried out by reading, analysing, and tracing sources through journals, books, and laws and regulations. The method of analysis used in this research is descriptive qualitative analysis, namely interpreting the data obtained in the form of sentence descriptions. The results of this study indicate that the concept of goods / services procurement is still not in line with the existing reality, where there are many problems in the procurement of goods / services both at the planning stage and the delivery of goods. So that in this study to minimise various problems in the procurement of goods / services, the government should adopt the principles of best practice in state financial management, so as to realise good governance.